2013
DOI: 10.2147/ott.s44564
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of cyclophosphamide and Chalone 19-peptide in experimental breast cancer

Abstract: BackgroundCyclophosphamide is a potent anticancer drug, but its clinical utility is limited because of its severe side effects, in particular liver damage. Chalone 19-peptide induces apoptosis of tumor cells and inhibits tumor growth. The present study investigated the antitumor effects of a combination of cyclophosphamide and Chalone 19-peptide in experimental breast cancer.MethodsAn animal model of breast cancer was developed, consisting of an MDA-MB-231 cell line implanted in the nude mouse. Eight doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, the possible combination with other compounds or factors altering the tumor environment makes CP an important cytostatic in anti-cancer therapy. Cancer cell apoptosis and suppression of tumor growth were observed after implantation of nude mice with MDA-MB-231 cells and treatment with a combination of CP with Chalone 19 peptide [ 31 ]. In turn, Agrawal et al found that insulin increases the cytotoxic effect of 5-fluorouracil and CP and enhances the apoptosis in the MCF-7 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible combination with other compounds or factors altering the tumor environment makes CP an important cytostatic in anti-cancer therapy. Cancer cell apoptosis and suppression of tumor growth were observed after implantation of nude mice with MDA-MB-231 cells and treatment with a combination of CP with Chalone 19 peptide [ 31 ]. In turn, Agrawal et al found that insulin increases the cytotoxic effect of 5-fluorouracil and CP and enhances the apoptosis in the MCF-7 cell line.…”
Section: Discussionmentioning
confidence: 99%